Adherence to WCRF/AICR guidelines for cancer prevention among breast cancer survivors: a preliminary observation from East coast of Peninsular Malaysia - Mohd Razif, Shahril; Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Lin, L.P; Aryati, Ahmad (2016)
The World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) guidelines encourage cancer survivors to follow its cancer prevention recommendations' This preliminary study evaluated adherence to the WCRF/AICR guidelines for cancer prevention among breast cancer survivors from East Coast of Peninsular Malaysia. Participants were 74 women aged 37 to 72 years who had been diagnosed with breast cancer according to American Joint Committee on Cancer (AJCC) stages I to III and completed conventional treatment at least six months before the interview. All participants were recruited from two main referral hospitals in Terengganu and Kelantan. Adherence scores for the WCRF/ AICR guidelines for body weight, physical activity, and diet were computed; assigning 1, 0.5 or O points to each of eight recommendations depending on the degree of adherence. Total adherence score was then categorised as high (score > 5), moderate (score < 5 to.>3) and poor (score < 3). Socio-demographic background and clinical data were compared by the total adherence score categories besides evaluating the adherence for each of the eight recommendations. This preliriina4r observation noted 66.2oh of breast cancer survivors highly adhered to the WCRF/AICR guidelines while only 1.4%o was categorised as poor adherence. The least adhered on physical activity (5%) and plant food intake (4%). However, differences in total score categories among these survivors were not attributed to thesocio-demographic background and clinical data (p>0.05). As a conclusion, the majority of breast cancer survivors from East Coast of Peninsular Malaysia adhered to the WCRF/AICR guidelines for cancer prevention. This preliminary report also addresses that strategies for-preventing cancer recurrence should emphasize on behavioural change to increase physical activities and intake of plant foods while maintaining a balanced diet.